Numerical evaluation of steel-rubber isolator with single and multiple rubber cores. (1st November 2019) - Rahnavard, Rohola; Thomas, Robert J.
Highlights: 14 FE models of steel-rubber isolator with a single and multiple cores were created. Static cyclic and dynamic time history analysis were applied. The results suggest, isolators with multiple cores outperform those with a single. Abstract: Seismic base isolators are used extensively in buildings, bridges, and critical infrastructure. During a seismic event, these isolators simultaneously experience the service loads and the base shear loads. It is therefore critical to understand their mechanical response under combined loading. In previous studies, researchers designed base isolators with the assumption that the axial loading is compressive. However, the baser isolators may also experience a tensile axial load during a seismic event. Few researchers have investigated the behavior of base isolators with combined axial tensile stress and base shear. This paper uses the finite element method to model the behavior of steel-rubber base isolators under combined axial tension or compression and base shear. The effect of the magnitude and direction of the axial load is investigated for base isolators subject to 375% shear strain. The numerical models suggest that the apparent stiffness of the base isolator increases when the axial load is tensile. The influence of the number and size of rubber cores in the steel-rubber base isolator is also investigated. The results suggest that base isolators with multiple radially-distributed rubber cores outperform those with a single central rubber core.